Skeletal muscle necrosis induced by a phospholipase A2 isolated from the venom of the coral snake Micrurus nigrocinctus nigrocinctus. - Arroyo Gutiérrez, Olga (1987)
1. The venom of the coral snake Micrurus nigrocinctus nigrocinctus was fractionated by reverse-phase high performance liquid chromatography and an acidic myotoxic phospholipase A2 was purified to homogeneity. 2. After intramuscular injection, the toxin induced rapid and drastic myonecrosis, as serum creatine kinase levels increased markedly, reaching their highest values by 1.5 hr. 3. Ultrastructural observations indicate that the plasma membrane was the first structure to be affected, with the presence of focal disruptions in its integrity. 4. Myofilaments were hypercontracted and formed dense clumps. Sarcoplasmic reticulum integrity was lost, as evidenced by the presence of many small vesicles in the cellular space. 5. Some mitochondria were swollen, whereas others contained dense intracristal spaces and flocculent densities. Moreover, some had only one membrane. 6. In conclusion, pathogenesis of myonecrosis induced by this phospholipase A2 is similar to that induced by crude Micrurus nigrocinctus nigrocinctus venom.